The Role of Specific Cellular Immune System in Chronic Hepatitis C - Ihsanil Husna; Nurul Akbar; Rino Alvani Gani; Unggul Budihusodo; Nanang Sukmana (The Indonesian Society for Digestive Endoscopy, 2004)
Hepatitis C virus is a RNA virus with very high speed replication. The clinical course of chronic hepatitis C is frequently asymptomatic like other hepatitis viruses. Infection of hepatitis virus will activate the immune system specifically as well as non-specifically. Mechanism of the immune system regulation is controlled by tissues consisting of antibodies cells and cytokines. In the process, all of the immune systems integrate and coordinate with the main agent-lymphocytes. Lymphocytes recognize antigens through the specific-surface antigen receptors. Following exposure to viral chronic hepatitis virus, viremia takes place within 1-2 weeks. In immuno-competent hosts, viremia will be preceded with the increase in transaminase enzyme and delayed seroconversion of antibodies will occur. Unlike other immunologic processes, these established antibodies are not protective in nature but serve only as the sign that someone has been infected by hepatitis C. In most cases of hepatitis C virus infection, this virus cannot be eradicated in the acute phase. Approximately 80-90% of acute infection progresses to be chronic infection and in 50% of the cases, there is an increase in transaminase enzyme that reveals that there is still liver cell damage. The degree of liver tissue damage in hepatitis depends on the number of virus infecting and the activity of cytotoxic T cells. Keywords: hepatitis C virus, humoral immune response,cellular immune response